Platinum group elements in proximal impactites of the Bukit Bunuh impact structure, Malaysia - Quek, L.X; Ghani, A.A.; Badruldin, M.H.; Saidin, M.; Harith, Z.Z.T.; Roselee, M.H. (2015)
The Bukit Bunuh in Malaysia has recently been identified as an impact structure after the discovery of possible impact-melt-like rocks and impact breccias from this area. The impact event is believed to have occurred around 1.34-1.84 Ma. Twelve impact-related rocks from this suspected impact structure were analysed in the present study for platinum group of element (PGE) content. The sample population includes proximal impactites (two impact-melt rocks and three impact breccias) and possible impact-related rocks (four mylonites) and basement granite (three in number). The results showed no observable clear distinction between the impactites and basement granite. Compared to other asteroid impact sites in the world, the impactites and impact-related rocks in the Bukit Bunuh structure clearly contain a lower concentration of PGEs. Even though previous studies reported possible evidences of shock metamorphism in the Bukit Bunuh structure and electrical resistivity survey favoured the presence of asteroid impact structure in this area as well, the absence of a clear projectile signature in our study on PGE hinders further discussion on the existence and nature of the impact. We suggest that the absence of any PGE signature in the Bukit Bunuh impactites could be indicative either of (1) an achondrite projectile, or (2) an oblique impact or (3) the presence of a volatile-rich layer.